The Concept of “Resentment” in Jean Améry’s Reflection on Time and History - Bugajewski, Maciej (Sensus Historiae, 2021)
In this article, I am trying to understand the reflection on resentment, presented in Jean Améry’s At the Mind’s Limits. Resentment is the feeling of the victim, demanding an attitude on the part of the perpetrator, which would have an effect of liberating the victim from this emotion. Améry analyzes the successive phases of the perpetrators’ respective actions. The most important are understanding that the crimes were a negation of the earlier historical identity of the nation to which the perpetrators belonged (negation) and the rejection of the entire historical heritage of the National Socialist period (negation of the negation). His reasoning is based on a philosophical reflection on time, which I juxtapose with Walter Benjamin’s considerations from the text “On the Concept of History”.